Existence and Exponential Stability for Random Impulsive Differential Evolution Equations - Ravikumar, K.; Banupriya, K.; Varshini, S.; Ramkumar, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
The paper is devoted to the study of existence and exponential stability of mild solutions of random impulsive differential evolution equations. The results are obtained using Leray-Schauder alternative fixed point theorem. Furthermore Exponential stability of the mild solution is established with certain sufficient conditions. An application is provided to illustrate the theory.